Pengaruh Pemberian Kombinasi Endomikoriza Glomus dan Jamur Trichoderma terhadap Produktivitas Tanaman Jagung (Zea Mays L.) The Effect Combination of Glomus Endomycorrhizal and Trichoderma on The Productivity of Corn (Zea Mays L.) - Nisa, Maghfirotun; Proborini, Meitini Wahyuni; Astarini, Ida Ayu (Metamorfosa: Journal of Biological Sciences, 2022)
The aim of the research was to determine the effect of the combination of Glomus endomycorrhizal and Trichoderma and the appropriate dose to increase the productivity of maize (Zea mays L.). The study was began with the propagation of Glomus endomycorrhizal spores in the green house of the Biology Study Program, Faculty of Mathematics and Natural Sciences, Udayana University and continued with endomycorrhizal spore screening, re-isolation of Trichoderma fungi and application of Glomus and Trichoderma endomycorrhizal spores to corn plants. The results showed that there was no significant difference between positive control (KNO 3 ) and endomycorrhizal and Trichoderma treatments on plant height, number of leaves, root length, ear length, ear diameter, ear wet and dry weight and shell weight and significantly different on the small size of the shells. Doses of 125 Glomus spores and 5 mL Trichoderma give the best results on the small amount of corn shells compared to other doses, so that the combination of endomycorrhizae and Trichoderma can be applied to reduce excessive chemical fertilizers.. Keyword : biofertilizer, growth, nutrient, productivity